Protection of an Individual’s Information Interest in the Light of Regulation No. 1049/2001 on Public Access to Documents of the European Parliament, the Council and the Commission - Tomaszewska, Katarzyna (LeXonomica, 2023)
The right to information, guaranteed by various legal acts, includes the right to access the content of documentation held by public entities. At the EU level, this right is regulated, inter alia, by Regulation (EU) No. 1049/2001 of the European Parliament and of the Council, dated 30 May 2001, regarding public access to documents of the European Parliament, the Council, and the Commission. The act outlines various measures and mechanisms that can be assumed to constitute instruments for protecting an individual’s information interest. This article provides an analysis of the relevant provisions, which regulate these instruments. The in-depth characterization aims to enable a stance on the correctness of the protective function attributed to access to EU documentation itself, as well as to its constituent elements. Povzetek Pravica do obveščenosti, ki jo zagotavljajo različni pravni akti, vključuje pravico do dostopa do vsebine dokumentacije, ki jo hranijo javni subjekti. Na ravni EU to pravico med drugim ureja Uredba (EU) št. 1049/2001 Evropskega parlamenta in Sveta z dne 30. maja 2001 o dostopu javnosti do dokumentov Evropskega parlamenta, Sveta in Komisije. V aktu so opisani različni ukrepi in mehanizmi, za katere se lahko domneva, da so instrumenti za zaščito posameznikovega informacijskega interesa. Ta članek vsebuje analizo ustreznih določb, ki urejajo te instrumente. Namen poglobljene karakterizacije je omogočiti stališče o pravilnosti zaščitne funkcije, ki se pripisuje samemu dostopu do dokumentacije EU, pa tudi njegovim sestavnim elementom.